Platycodin D Inhibits Lipogenesis through AMPKα-PPARγ2 in 3T3-L1 Cells and Modulates Fat Accumulation in Obese Mice - Lee, Eun Jeong; Kang, Minseok; Kim, Yeong Shik (Planta Medica, 2012)
Platycodin D (PD) has been reported to control obesity in vivo. This study investigated the molecular mechanism of PD, focusing on its ability to decrease the expression of adipogenic factors through AMP-activated protein kinase α (AMPKα) in adipocytes and its ability to prevent abdominal fat accumulation in high-fat diet-induced obese C57BL/6 mice. The inhibitory effect of lipid accumulation in 3T3-L1 cells was measured by Oil Red O staining, reverse transcription-polymerase chain reaction (RT-PCR), and Western blotting. To determine the antiobesity effect in vivo, one group of mice were given a normal diet and the others were fed a high-fat diet for 8 weeks. The high-fat diet mice were then assigned to one of three subgroups: aminoimidazole carboxamide ribonucleotide (AICAR), vehicle, and PD. PD significantly reduced fat accumulation by inhibiting adipogenic signal transcriptional factors, such as peroxisome proliferator-activated receptor γ2 (PPARγ2) and CCAAT/enhancer binding protein α (C/EBPα), which functions via AMPK signaling, in vitro. PD reduced both body weight and fat volume; consequently, lipid metabolism was improved by increasing AMPKα, similar to AICAR, and reduced PPARγ2 and C/EBPα expression in adipose tissue. The results suggested that PD could be used to decrease the expression of adipogenic factors related to the AMPK pathway. Hence, PD could be an alternative treatment for controlling obesity by downregulating lipid accumulation.
Keywords: abdominal obesity; adipocytes; adipogensis; platycodin D; Platycodon grandiflorum; Campanulaceae